Cost-Effectiveness of Community Pharmacist-Led Smoking Cessation Programs (2015–2025): A Meta-Analysis Review - Firdaus, Favian Rafif; Yulnanda, Alsita Salsabila (Yayasan Jompa Research and Development, 2025)
To systematically review the types of economic evaluations used for community pharmacist-delivered smoking cessation programs and to conduct a meta-analysis of their clinical effectiveness. Methods A systematic search was conducted in PubMed, Scopus, Science Direct, EBSCO, and ProQuest for studies published between 2015 and 2025. The participant criteria are active smokers aged over 18 years, not limited by gender, and the program focuses on community settings. Full economic evaluations of pharmacist-led smoking cessation programs for adults were included. Study quality was assessed using the CHEERS 2022 checklist. Clinical effectiveness data were pooled using a random-effects meta-analysis. The protocol was registered with PROSPERO (CRD420251117242). Results out of 681 identified records, four studies met the inclusion criteria, encompassing more than 1,300 participants. Interventions were conducted in Spain, Canada, Malaysia, and the USA. The majority used cost-effectiveness analyses and reported significant improvements in smoking cessation rates. Meta-analysis showed that pharmacist-led programs significantly improved quit rates (pooled OR = 2.74; 95% CI: 1.83–4.11; p < 0.001) with low heterogeneity (I² = 8.8%). ICERs were consistently below accepted cost-effectiveness thresholds. Based on a threshold analysis using a WTP of CAD20,000 per QALY, the intervention by Phillips et al. remains cost-effective. The intervention would remain below the threshold unless total costs increased by 23.6% or QALY gains reduced by more than 18%. Conclusion community pharmacist-delivered smoking cessation programs are a clinically effective and economically favorable public health strategy. Policymakers should consider establishing reimbursement models to facilitate their broader implementation.